Le numérique, indispensable émancipateur de la mobilité électrique ? - Manon Eskenazi; Magali Pierre; Virginie Boutueil; Caroline Escoffier (Netcom)
On several occasions in automobile history, the electric vehicle has failed to emerge as a desirable technological innovation in the face of the competition stemming from an increasingly efficient conventional vehicle. In recent years however, it has been the object of renewed interest from automakers and public authorities, especially for environmental reasons. Our twofold purpose here is to discuss whether the diffusion of digital technologies may create, for the first time in the history of the electric car, the conditions for its large-scale adoption by car users, and to analyse the social effects of such a transformation of practices. This paper is based on two sociological surveys of electric vehicle users carried out in 2015. The first survey was carried out along with the deployment of a nationwide fast-charging network and analysed the insertion of public charging into mobility practices. The second survey focused on users of a carsharing service using small electric vehicles in the Isere district. In the light of the results of these two surveys, we will show why the deployment of new-generation electric vehicles, supported by the diffusion of digital tools, is part of a complex dynamic process of transformation of mobility practices by connected devices that provide real-time access to up-to-date, customised information and form a community of users around this technological object, all the while relying on skills that are likely to exclude portions of potential users.